Fundamentals of Entrepreneurship (ENT300) Banana House / Hilimena Anak Jeffery Juing... [et al.] - Jeffery Juing, Hilimena; Kallam, Norfazilah; James, Shally; Lewat, Nathasha Essa; Getruda, Condrad; Asok, Juliah; Nasfurizan, Dayang (2015)
Banana House is our company's name, which consists of seven members to form partnership. Each partner contributes particular amount of capital which has been agreed in the contract. The major business activity is selling banana coated. Our shop is located Jalan Canna, 93350 Tabuan Tranquility, Kuching Sarawak. The main purpose we choose this area because this area is very strategic with many people near with our shop. We will provide the best and fast services to our customers. There are no passive partners in this business and all of us are assigned with the respective business management posts. We assigned Hilimena Anak Jeffery Juing as our General Manager,Norfazilah binti Kallarn as our Marketing Manager, Shally Anak James and as our Assistant Marketing Manager, Nathasha Essa Lewat as our Operation Manager and Condrad Getruda as our Assistant Operation Manager Juliah Asok as our Administration Manager and Dayang Nasfurizan binti Abang Abdul Manap as our Financial Manager. All of us are assigned based on our respective education qualification, experience, skills and capability.